Lack of head sparing following third-trimester caloric restriction among Tanzanian Maasai - Powell, Christopher D. (2020)
The reduction of food intake during pregnancy is part of many cultural and religious traditions around the world. The impact of such practices on fetal growth and development are poorly understood. Here, we examined the patterns of diet intake among Maasai pregnant women and assessed their effect on newborn morphometrics. We recruited 141 mother-infant pairs from Ngorongoro Conservation Area (NCA) in Northern Tanzania and quantified dietary intake and changes in maternal diet during pregnancy. We obtained measurements of body weight (BW) and head circumference (HC) at birth. We found that Maasai women significantly reduced their dietary intake during the third trimester, going from an average of 1601 kcal/day during the first two trimesters to 799 kcal/day in the final trimester. The greatest proportion of nutrient reduction was in carbohydrates. Overall, 40% of HC Z-scores of the NCA sample were more than 2 standard deviations below the WHO standard. Nearly a third of neonates classify as low birth weight (< 2500g). HC was smaller relative to BW in this cohort than predicted using the WHO standard. This contrasts markedly to a Tanzanian birth cohort obtained at the same time in an urban context in which only 12% of infants exhibited low weight, only two individuals had HC Z-scores < 2 and HC’s relative to birth weight were larger than predicted using the WHO standards. The surprising lack of head sparing in the NCA cohort suggests that the impact of third trimester malnutrition bears further investigation in both animal models and human populations, especially as low HC is negatively associated with long term health outcomes.